Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Guru PAUD Kabupaten Seluma - Sudriyanti Putri; Edwarman Edwarman (UNIVED Press, 2023)
The purpose of this study was to analyze the factors that influence the performance of Kick Taq PAUD teachers in Seluma Regency. Human resources are the only resources that have a sense of mind, feelings, skills, desires, encouragement, knowledge, power and work. Performance is an activity carried out to carry out, complete tasks and responsibilities in accordance with the expectations and goals that have been set, performance is often referred to as achievement which is the result of a job and the contribution of human resources to the organization. The data collection analysis method used in this study was a questionnaire. The questionnaire was assessed using a Likert scale, while the analysis method was qualitative, quantitative and the analytical tool was a rating scale. The results of the study of three factors that affect the performance of PAUD Kick Taq teachers in Seluma Regency, individual variables, organizational variables, and psychological variables, that the most dominant factor affecting the performance of Kick Taq PAUD teachers in Seluma Regency is the psychological variable that received the perception of the respondents with the criteria of strongly agreeing. Meanwhile, the second factor of the individual variable received the perception of agreeing, meaning that the individual variable also affected the performance of the PAUD Kick Taq teacher in Seluma Regency, and the lowest dominant factor was the organizational variable, namely the reward but still received the perception of the respondent with the criteria of agreeing.